Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Perusahaan Sub Sektor Konstruksi di Bursa Efek Indonesia - Iman Rusdianto; Bambang Waluyo; Fatimah Fatimah (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2020)
This research aims to examine the effects of current ratio (CR), debt to assets ratio (DAR), total assets turnover (TAT), and net profit margin (NPM) at the company's profit growth construction on the Indonesia Stock Exchange (IDX). Data were collected from the financial statements of 6 construction sub-sector companies on the Indonesia Stock Exchange with a purposive sampling technique. The regression panel analysis found that DAR and NPM have a positive significance to the profit growth of construction companies, while CR and TAT insignificant. The ability of the model to explain the dependent variables is 38.64% indicating that many other factors are also thought to affect profit growth. This study recommends that DAR and NPM can be used as a useful reference for predicting the company's future profit growth.